PANCREATIC DUCT STONES - Khan, Mohammad Naeem; Raza, Syed Shahmeer; Hussain, Amer Kamal; Nadeem, Muhammad Daniyal; Ullah, Farhan (Journal of Ayub Medical College Abbottabad, 2017)
Stones of pancreatic ductal origin are often linked to chronic pancreatitis. Chronic pancreatitis appears to exist in the presence of such calculi upon radiology. Having said that, pancreatic ductal stone due to biliary causes (origin), in face of acute pancreatitis, is rare. To the best of our knowledge this was the first case of its kind presented to our hospital in recent past. A 25-year-old female presented to the emergency department of our hospital with an acute episode of pancreatitis. Computerized tomography (CT) scan, endoscopic retrograde cholangiopancreatography (ERCP) & magnetic resonance cholangiopancreatography (MRCP) concluded acute pancreatitis (AP) with dilated main pancreatic duct left side branches and intra ductal calculi. The findings were not suggestive of any chronic pancreatitis. Conservative treatment was given for the episodic attack of AP. After the episode resolved, an exploration and extraction of the pancreatic ductal calculus was performed successfully. The pancreatic duct stones were removed by lateral pancreaticojejunostomy (partington-rochelle procedure). The patient made a remarkable recovery after the procedure and was perfectly healthy and well-oriented in time and space at 4-months follow up. Acute pancreatitis is an inflammatory condition of pancreas, when, associated with pancreatic duct stones a lateral pancreaticojejunostomy is done, which, results in better outcomes decreasing the mortality and morbidity. Acute pancreatitis due to ductal calculi is rare for which extraction is safe after resolution of the episode of AP. Studies need to be carried out to look for the outcome and the effectiveness of the procedure, when, specifically and specially done for this condition. Keywords: Calculi; Pancreatic Duct Stones; MRCP, ERCP; Acute Pancreatitis